Between Spirituality and Popularity: Commodification and Shifting Authority in Digital Preaching - Shofam Amim Mujadid; Cecep Castrawijaya (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
Digital transformation has shifted the practice of da'wah from a physical-based religious communication to a media ecosystem influenced by platform logic, algorithms, and popularity culture. This study aims to analyze the dilemma of digital da'wah in maintaining a spiritual orientation while adapting to the demands of visibility in the digital space. This study uses a qualitative approach with a library research method through a critical review of 28 scientific sources published between 2018 and 2025, which include studies on digital religion, the mediatization of religion, digital religious authority, and the commodification of da'wah. Data are analyzed interpretively through a process of concept identification, comparison of findings, and theoretical synthesis. This study found that the main dilemma of digital da'wah lies not only in media changes, but in the shift in the logic of religiosity: from an orientation towards spiritual development to the demands of digital performativity. The main finding of this study is a conceptual model that maps nine dimensions of tension between spirituality and popularity, including the purpose of da'wah, message character, role of da'wah, source of authority, media, system logic, audience relations, content production, and social impact. The model demonstrates that digital da'wah undergoes a negotiation between the authenticity of religious values ​​and the mechanisms of the attention economy, so that religious authority is no longer solely constructed through scholarly legitimacy, but also through visibility, interaction, and resonance within digital networks. This research implies the need for a digital da'wah strategy that integrates technological adaptation with maintaining message depth, communication ethics, and the sustainability of spiritual development.